Optimization of Waste Cooking Oil Transesterification in a Continuous Microwave Assisted Reactor - Mohd Affandi, Mohd Ali; Jolius, Gimbun; Cheng, C. K.; R. M., Yunus (The Italian Association of Chemical Engineering - AIDIC, 2015)
This paper presents the design and performance evaluation of a continuous microwave assisted reactor (CMAR) system to produce biodiesel from the transesterification of waste cooking oil (WCO). The labfabricated CMAR employed an integrated proportional-integral-derivative controller for accurate temperature and reactant flowrate controls. The fatty acid methyl esters (FAME) contents in the sample were determined using gas chromatography mass spectrometry (GC-MS). The results from two-level factorial design showed that the methanol to oil molar ratio, amount of NaOCH3 catalyst and reaction time affected the biodiesel conversion markedly, with the significance of 45.99 %, 6.76 % and 3.21 %. The optimum biodiesel conversion of circa 97.83 % was achieved at 0.68 wt% of catalyst loading, 11.62:1 of methanol to oil molar ratio and 4.47 min of reaction time using the response surface method (RSM) generated by the Box Behnken design. Experimental validation of the optimum condition showed an excellent adherence, with a minimum deviation of 0.88 % in three replicates. The biodiesel produced in this work also met the specification of ASTM D6751.